Integrated management of root knot nematode, Meloidogyne incognita in ginger - and G.S. DAVE, I. VADHERA, S.P. TIWARl (Indian Phytopathology, 2002)
Amending the soil with different oil cakes was found to be effective in reducing the soil population as well as root gall formation in ginger crop. Highest yield and maximum reduction in soil population was recorded in neerncake treated plots. Denematization of ginger rhizomes at 45Â°C for three hours+ summer ploughing and covering of soil with polythene trap between May, 15th to 30th gave significantly higher (59.06%) yield and reduction (soil 71.58 and ginger rhizomes, 59.06 per cent) in nematode population.